On the fauna of the Coleophoridae of Mexico (Lepidoptera: Coleophoridae) - H. W. Van der Wolf (SHILAP, 2017)
16 new species are described from Mexico: Coleophora papalotontli van der Wolf, sp. n., C. powelli van der Wolf, sp. n., C. saltoella van der Wolf, sp. n., C. tehuacanella van der Wolf, sp. n., C. coahuila van der Wolf, sp. n., C. popoloca van der Wolf, sp. n., C. bajacalsur van der Wolf, sp. n., C. penicillata van der Wolf, sp. n., C. pueblana van der Wolf, sp. n., C. catavinae van der Wolf, sp. n., C. puntaprietae van der Wolf, sp. nov., C. yagul van der Wolf, sp. n., C. bajacaliforniae van der Wolf, sp. n., C. iztac van der Wolf, sp. n., C. incerta van der Wolf, sp. n. and C. mexicacopa van der Wolf, sp. n. Of C. yagul the foodplant is given and the larval case described and illustrated. The female genitalia of C. mexicana Landry, 1994 are described and illustrated for the first time. C. versurella Zeller, 1849 is reported from Mexico for the first time.